Skin-Related Properties and Constituents from the Aerial Parts Extract of Persicaria senticosa. (21st December 2020) - Choi, Yun-Hyeok; Lee, Jae Yeon; Lee, Ji Eun; Jung, Yeon Woo; Jeong, Wonsik; Hong, Seong Su; Cho, Young-Rak; Choi, Chun Whan
Abstract : In the course of screening for cosmetic ingredients by measuring antioxidant and antiwrinkle and whitening and anti-inflammatory activities, skin-related activity was tested using 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging, 2, 2 ′ -azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging, elastase inhibition, tyrosinase inhibition, and nitric oxide assay. Several Polygonaseae extracts were found to show potent activity. The results showed that the Persicaria senticosa methanolic extract has the 1, 1diphenyl-2picrylhydrazyl (DPPH) and ABTS radical scavenging activities (IC50 61.0 and 17.5 μ g/mL). In the elastase inhibition assay and nitric oxide assay, the IC50 of methanolic extract of Persicaria senticosa was 739.7 μ g/mL and 71.8 μ g/mL. The Persicaria senticosa 70% ethanolic extract partitioned with n-hexane, CH2 Cl2, EtOAc, n-BuOH, and aqueous fractions. The purification of EtOAc soluble layer was by column chromatography separation and MPLC analysis of Compounds 1-7 . It was identified as loliolide (1 ), quercetin-3-O-glucoside (2 ), quercetin-3-O-glucuronide (3 ), 4-methoxy caftraric acid (4 ), kaempferol-3-(6-methylglucuronide) (5 ), quercetin-3-(6-methylglucuronide) (6 ), and quercetin (7 ). Structure was elucidated by a combination of 1D and 2D NMR and MS spectrometry as well as comparison with reported literatures. Radical scavenging effect on DPPH, tyrosinase inhibition, and nitric oxide assay on several compounds from Persicaria senticosa was found to show potent activity. The results showed that Compound 7 has the NO assay (IC50 29.7 μ M). For DPPH, the IC50 of Compounds 2, 3, 5, and 7 was 39.6, 31.2, 37.0, and 22.7 μ M. In tyrosinase inhibitory activity, the IC50 of Compound 7 was 14.3 μ M.